Aspects of string theory: higher-spins, pure spinors in AdS and ambitwitstors - Flores, Henrique dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
In this thesis we study both limits of the AdS/CFT correspondence: the phase space of higher-spin theories, and the insertion of vertex operators in string correlation functions of the pure spinor formulation in $AdS_{5} \times S^{5}$ background. We also compute the equations of motion for Ramond sector of the RNS heterotic ambitwistor string. The study the phase-space of free higher-spin theories uses a formulation obtained from twistors by Penrose and hints the presence of a non-local conformal symmetry. The string scattering in AdS is studied with the BV formalism, appropriate for this background given that the b-ghost is non-holomorphic; we write the amplitude with the insertion of a beta-deformation vertex. For the heterotic ambitwistor system, we obtain the supersymmetry algebra of this theory.

Nesta tese, nós estudamos ambos limites da correspondência AdS/CFT: o espaço de fase das teorias de spin alto, e a inserção de operadores de vértice nas funções de correlação da corda de espinores puros escrita no background $AdS_{5} \times S^{5}$. Nós calculamos também as equações de movimento do setor de Ramond para a corda ambitwistor heterótica na descrição RNS. O estudo do espaço de fase das teorias de spin alto usa a formulação obtida por Penrose e dá indícios da presença de uma simetria conforme não-local. A amplitude de espalhamento em AdS é estudada com o formalismo BV, apropriado para este background onde o fantasma b não é holomórfico; nós escrevemos a amplitude com a inserção de um vértice de deformação beta. Para o sistema heterótico, nós obtemos as transformações de supersimetria da teoria.
Aspectos da teoria de cordas: spins altos, espinores puros em AdS e ambitwistors
Keywords: Física; Teoria de cordas; Teoria quantica de campos